2003
DOI: 10.1101/gr.1507303
|View full text |Cite
|
Sign up to set email alerts
|

Application of DNA Microarrays to Study the Evolutionary Genomics of Yersinia pestis and Yersinia pseudotuberculosis

Abstract: Yersinia pestis, the causative agent of plague, diverged from Yersinia pseudotuberculosis, an enteric pathogen, an estimated 1500–20,000 years ago. Genetic characterization of these closely related organisms represents a useful model to study the rapid emergence of bacterial pathogens that threaten mankind. To this end, we undertook genome-wide DNA microarray analysis of 22 strains of Y. pestis and 10 strains of Y. pseudotuberculosis of diverse origin. Eleven Y. pestis DNA loci were deemed absent or hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
151
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(154 citation statements)
references
References 42 publications
3
151
0
Order By: Relevance
“…Based on these analyses, it was estimated that Y. pestis diverged from its Y. pseudotuberculosis ancestor only within the last 10,000-20,000 years (Achtman et al 1999(Achtman et al , 2004. Further comparative genomics analyses confirmed a high degree of genomic identity between the two species (Chain et al 2004;Hinchliffe et al 2003;Zhou et al 2004). The close phylogenetic relationship of Y. pseudotuberculosis and Y. pestis implies that the change from a comparatively benign foodand water-borne enteric pathogen to a highly virulent, arthropod-borne systemic pathogen occurred quite recently in evolutionary terms and is based on relatively few genetic differences (Hinnebusch 1997;Lorange et al 2005).…”
Section: Y Pestis a Recently Emerged Clone Of Y Pseudotuberculosismentioning
confidence: 79%
“…Based on these analyses, it was estimated that Y. pestis diverged from its Y. pseudotuberculosis ancestor only within the last 10,000-20,000 years (Achtman et al 1999(Achtman et al , 2004. Further comparative genomics analyses confirmed a high degree of genomic identity between the two species (Chain et al 2004;Hinchliffe et al 2003;Zhou et al 2004). The close phylogenetic relationship of Y. pseudotuberculosis and Y. pestis implies that the change from a comparatively benign foodand water-borne enteric pathogen to a highly virulent, arthropod-borne systemic pathogen occurred quite recently in evolutionary terms and is based on relatively few genetic differences (Hinnebusch 1997;Lorange et al 2005).…”
Section: Y Pestis a Recently Emerged Clone Of Y Pseudotuberculosismentioning
confidence: 79%
“…We infer that these molecular grouping represent distinct bacterial populations. Independent support for the existence of these populations also can be deduced from other molecular analyses, which have examined subsets of the diversity examined here (3)(4)(5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 93%
“…Based on a correlation between the current geographical sources of the biovars and the inferred sources of historical plague, Devignat (2) suggested that Antiqua caused Justinian's plague and Medievalis caused the Black Death. Each of the biovars seems to be distinct according to the genomic patterns of IS100 insertion elements, supernumerary DNA islands, or multilocus variable number of tandem repeat analysis (MLVA) (3)(4)(5)(6)(7)(8). However, direct evidence uniquely associating any of the biovars with historical plague is lacking.…”
Section: P Lague Decimated the Human Population Of Europe And Northmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative genomic hybridizations (CGHs) by DNA micro-and macroarrays have been employed to reveal the evolution and function of pathogenicity in genomic terms in organisms such as Escherichia coli (Dobrindt et al, 2003;Carter et al, 2008), Yersinia pestis (Hinchliffe et al, 2003), Yersinia pseudotuberculosis (Zhou et al, 2004), Xylella fastidiosa (Koide et al, 2004), Campylobacter jejuni (Pearson et al, 2003), Streptococcus agalactiae (Brochet et al, 2006) and Streptococcus pneumoniae (Obert et al, 2006). The results of these studies indicate that mobile genetic elements such as phages, transposons and GIs contribute to pathogenicity acquisition and environmental adaptation.…”
Section: Introductionmentioning
confidence: 99%